Risk factors for implant failure of custom-made acetabular implants in patients with Paprosky III acetabular bone loss and combined pelvic discontinuity - Fröschen, Frank Sebastian; Randau, Thomas M.; Gravius, Nadine; Wirtz, Dieter C.; Gravius, Sascha; Walter, Sebastian G. (Technology and health care, 2022)
BACKGROUND: Severe acetabular bone loss in revision total hip arthroplasty (RTHA), both with or without pelvic discontinuity, remains a great challenge in orthopaedic surgery. OBJECTIVE: The aim of this study was to evaluate risk factors for failure of custom-made acetabular implants in RTHA. METHODS: Seventy patients with severe acetabular bone loss (Paprosky Type III) and pelvic discontinuity, who required RTHA, were included in our study. All prostheses were constructed based on a thin-layer computed-tomography (CT) scan of the pelvis. The treatment was considered unsuccessful in the event of periprosthetic joint infection (PJI) or aseptic loosening (AL) with need for explantation of the custom-made acetabular implant. RESULTS: The average follow-up was 41.9 ± 34.8 months (range 1.5–120). Implant survival at last follow-up was 75.7% (53 of 70). Explantation was necessary in 17 cases (15 PJI; 2 AL). Previous PJI as reason for RTHA (p= 0.025; OR 3.56 (95% CI: 1.14; 11.21)), additional revision of femoral components (p= 0.003; OR 8.4 (95% CI: 1.75; 40.42)), rheumatoid disease (p= 0.039; OR 3.43 (95% CI: 1.01; 11.40)), elevated preoperative CRP > 15.2 mg/l (p= 0.015; AUC: 0.7) and preoperative haemoglobin < 10.05 (p= 0.022; AUC: 0.69) were statistically significant risk factors associated with treatment failure. Age and BMI were not statistically significant contributing to implant failure. CONCLUSION: Risk factors for treatment failure were a previous PJI, additional revision of femoral component, rheumatoid disease, elevated preoperative CRP and low preoperative haemoglobin. Awareness of these risk factors will help to improve future treatment standards.
Gesehen am 24.06.2024